Diskresi Pemberhentian Sekretaris Dewan Perwakilan Rakyat Daerah Kabupaten Jember - Rudi Adrianus Riri Hena (JURNAL RECHTENS, 2017)
The Regional Government Act does not contain regulatory norms and provides guidance on the submission mechanism of DPRD secretary candidates, including not providing direction for the approval process and the maximum period of approval process. Even Government Regulation No. 18 of 2016 on Regional Devices that should describe more technical Law on Regional Government did not also regulate the mechanism, process or period of time. This certainly causes difficulties in its implementation. Given the uncertainty, the Regent of Faida took discretion to temporarily appoint officials as executors of the secretariat of the DPRD. Faida also mentioned that with the revocation of Local Regulation Number 15 Year 2008 regarding Organization  and  Working  Procedure  of  Jember  Regency,  the  arrangement  of  regional apparatus must adjust Article 3 of Regional Regulation Number 3 Year 2016, effective effective January 2, 2017. The juridical consequence of this adjustment is that All regional apparatuses including Farouq's parliamentary secretary should be first-line. This is because the regional devices are still formed based on perda that have been revoked. Its own discretion of the legal basis is the provision of Law Number 30 Year 2014 on Government Administration.